2010
DOI: 10.1021/jp101264m
|View full text |Cite
|
Sign up to set email alerts
|

Metal Cation Dependence of Interactions with Amino Acids: Bond Energies of Rb+ to Gly, Ser, Thr, and Pro

Abstract: The interactions of rubidium cations with the four amino acids (AA), glycine (Gly), serine (Ser), threonine (Thr), and proline (Pro), are examined in detail. Experimentally, the bond energies are determined using threshold collision-induced dissociation of the Rb(+)(AA) complexes with xenon in a guided ion beam tandem mass spectrometer. Analyses of the energy dependent cross sections include consideration of unimolecular decay rates, internal energy of reactant ions, and multiple ion-molecule collisions. 0 K b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
102
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(118 citation statements)
references
References 66 publications
15
102
1
Order By: Relevance
“…3.8 left) and cis-bis (glycinato)-platinum (Pozhidaev et al 1975;Fig. 3 In addition to the salts listed in Table 3.1, Bowman et al (2010) reported a rubidium salt of glycine (along with serine, threonine, and proline analogs) by mass spectrometry, although no crystals suitable for structure analysis were obtained.…”
Section: Glycinementioning
confidence: 99%
See 1 more Smart Citation
“…3.8 left) and cis-bis (glycinato)-platinum (Pozhidaev et al 1975;Fig. 3 In addition to the salts listed in Table 3.1, Bowman et al (2010) reported a rubidium salt of glycine (along with serine, threonine, and proline analogs) by mass spectrometry, although no crystals suitable for structure analysis were obtained.…”
Section: Glycinementioning
confidence: 99%
“…Among these were the sodium and potassium salts of phenylalanine, tyrosine, and tryptophan (Ruan and Rodgers 2004), whose molecular structures were assessed via mass spectroscopy. Likewise, lithium, sodium, and potassium prolinates as well as rubidium prolinate (Bowman et al 2010) were characterized by the same method.…”
Section: Valine Leucine and Isoleucinementioning
confidence: 99%
“…Relative measurements of the interactions of lithium [72][73][74] and sodium 73,75) cations with most amino acids have been performed using the kinetic method, 76,77) with absolute thermochemistry obtained using GIBMS for all the alkali metal cations with several amino acids: glycine (Gly), [78][79][80][81][82] proline (Pro), [81][82][83] serine (Ser), 81,82,84) threonine (Thr), 81,82,84) cysteine (Cys), 82,85) methionine (Met), 86) aspartic acid (Asp), asparagine (Asn), glutamic acid (Glu), glutamine (Gln), 25,87) phenylalanine (Phe), tyrosine (Tyr), and tryptophan (Trp). 88) In all cases, the TCID experiments yield quantitative BDEs that are generally consistent with quantum chemical values.…”
Section: Alkali Metal Cation Binding To Amino Acidsmentioning
confidence: 99%
“…As for any other ligands, 5) the BDEs increase as the size of the metal cation decreases. 81,82) This is shown in Fig. 3 for Na + and K + , the alkali metals for which the most data are available, largely because these are the most relevant biologically.…”
Section: Alkali Metal Cation Binding To Amino Acidsmentioning
confidence: 99%
“…Naturally occurring amino acids are well known to exist as zwitterions in the solid state and aqueous solution within a wide range of pH values, whereas in the gas phase the isolated amino acids are exclusively in the canonical form. However, interactions with other molecules or ions can play a key role in stabilizing the zwitterionic form of amino acids, as demonstrated by many previous studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 96%